Treatment of sugarcane vinasse from cachaça production for the obtainment of Candida utilis CCT 3469 biomass - Santos, Jéssica Ferreira dos; Canettieri, Eliana Vieira [UNESP]; Souza, S. M.A.; Rodrigues, R. C.L.B.; Martínez, Ernesto Acosta (Elsevier, 2019)
Ethanol and “Cachaça” production processes generate considerable amounts of residues known as vinasse. The indiscriminate disposal of this waste represents a potential risk to both surface water and groundwater, soil, animals, and ultimately the entire environment. This work describes an alternative to reduce the environmental impact through cachaça vinasse management practices by using it as a culture medium for the growth of Candida utilis CCT 3469 to produce biomass, replacing the conventional production from cane molasses. For that both, the raw and vacuum evaporated, vinasses from cachaça were treated by using different pH adjustments and activated charcoal adsorption (2.5%). The vinasses treated at pH 6.0 were selected to produce Candida utilis CCT 3469 biomass (2.25 g L−1). In this case, higher values of volumetric biomass productivity (0.08 gL−1 h−1)and biomass yield (0.13 gg−1)were obtained, as also for the higher specific rates for glucose consumption (1.354 gglucose gcell−1 h−1), fructose consumption (0.811 gfructose gcell−1 h−1)and biomass (0.616 h−1). The ratio values for BOD/COD (0.02)characterized the vinasse as an effluent of difficult degradation and biological treatability. Probably this fact favored the obtainment of yeast biomass in the treated vinasse at the lowest concentration factor.
Keywords: Cachaça; Candida utilis CCT 3469; Treatment; Vinasse; Yeast biomass